Independence of Female Judges in the Perspective of Islamic Law - Gema Rahmadani; Muhammad Faisal (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
The purpose of this article is to provide the public with an overview of the independence of female judges as bearers of judicial power. Under positive law, gender does not matter, so both men and women can become judges. This is in contrast to scholars who have concluded that women's lack of intelligence makes their testimony half as valuable as that of men. Women cannot hold judicial positions because they are mentally weak. This is because the job requires impeccable reasoning. The judiciary is the legal vehicle through which judges carry out their duties to hear and decide cases submitted to them in a manner that is free from the interference or influence of other institutions of power. On the side of the executive or legislative bodies. Situations vary depending on your opinion. This article uses a normative type of research, and the provisions of the findings of this study indicate that although Indonesian society is famous for its very high normative approach to religion, judges who decide cases in Indonesia still have a sense of justice in society. Obedient to religious norms.